MENATA KOMUNIKASI PADA MEDIA SOSIAL ONLINE UNTUK MENGHINDARI JERAT HUKUM - Mahayoni Mahayoni (Universitas Bunda Mulia, 2015)
AbstrakCurrently the development of on-line world of social media in Indonesia is very rapid. Now even online social media becomes an integral part of society. In addition to the ease of getting the network, the price is more affordable for most people. Unfortunately, the availability of facilities and infrastructure is not accompanied by the readiness of regulation capable of managing communication through social media. Without a rule that organizes and directs users online media resulted in the omission of the online media communities. This situation is exacerbated when directly ahead of the 2014 presidential election through the smear campaign and criticizes each other, mutual blasphemous, to the speech of hatred. Unfortunately, despite the elections have passed, but the use of